2013
DOI: 10.1186/1471-2407-13-437
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of Her4 receptor isoform expression in triple-negative and Her2 positive breast cancer patients

Abstract: BackgroundNot only four but rather seven different human epidermal growth factor receptor related (Her) receptor tyrosine kinases (RTKs) have been described to be expressed in a variety of normal and neoplastic tissues: Her1, Her2, Her3, and additionally four Her4 isoforms have been identified. A differential expression of Her4 isoforms does not, however, play any role in either the molecular diagnostics or treatment decision for breast cancer patients. The prognostic and predictive impact of Her4 expression i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…In addition, studies have shown that cytoplasmic HER4 is linked with improved survival of breast cancer patients [12, 47]. In our cohort study, we also demonstrated a similar pattern that high level of cytoplasmic HER4 had a better prognosis in HER2 positive breast cancer patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, studies have shown that cytoplasmic HER4 is linked with improved survival of breast cancer patients [12, 47]. In our cohort study, we also demonstrated a similar pattern that high level of cytoplasmic HER4 had a better prognosis in HER2 positive breast cancer patients.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study of HER4 isoform expression in breast cancer demonstrated a correlation between JM-a isoforms (CYT1 and CYT2) with longer patients' survival [12]. In addition, studies have shown that cytoplasmic HER4 is linked with improved survival of breast cancer patients [12, 47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are potentially oncogenic ERBB4 mutations in non-small cell lung cancer (9), and it has been reported that HER4 is overexpressed in human colon cancer and enhances cellular transformation (10). In addition, HER4 promotes breast cancer cell proliferation, mediates acquired resistance to ERBB2 inhibitors and may serve as a prognostic marker in patients with breast cancer (11)(12)(13)(14). However, the role of HER4 in CRC remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Divergence of signaling processes incited by the four ERBB4 isoforms may explain the discordance in the ERBB4 cancer literature: most studies fail to consider these isoforms separately, and the isoform(s) expressed and subcellular localization of ERBB4 have an impact on prognosis (11, 12). …”
Section: Introductionmentioning
confidence: 99%